Clinical, biochemical, and radiologic findings of girls with early puberty attended at a public hospital in Lima, Peru - Cabello-Sánchez, Almendra (2024)
Objective: To describe the clinical, biochemical, and radiologic findings of girls with early puberty (EP) attended at a public hospital in Lima, Peru. Methods: This is a case series study that results from the review of clinical charts of girls diagnosed of (EP). Patients with peripheral EP, isolated thelarche and malformations were excluded. The Z-IMC, Z-genetic height, Z-height, and projected adult final height (PAFH) were calculated. The t-Student, Wilcoxon and Shapiro-Wilk tests were calculated using STATA version 17, a p values < 0.05 was considered statistically significant, the study was approved by the IRB of UPCH and HCH. Results: We reviewed 86 charts; mean age was 8,16±1.09 years and mean bone age was 10.33±1.27 years (p≤0.001). We found M2(19.7%), M3(59.3%) and M4(20.9%). Normal weight (27.9%), overweight (30.2%) and obesity (41.8%). Median LH was 0.6 (RIQ:0.4-1.8) and median FSH was 3.4 (RIQ:2.1-5.2). Conclusion: Chronologic age at diagnosis was late with a bone age higher than chronologic age. Height of girls compared to genetic height was higher. PAFH was lower than genetic height. Most of the girls presented with advanced breast development, overweight and obesity.